Assessing Knowledge, Attitude, and Practices on Hospital Acquired Infections Control by Anaesthesia Practitioners in the Operating Theatres of the Tamale Teaching Hospital (TTH); Ghana - Danaah Malick, Martin Mumuni; Akpa, Edem Yao; Bamaalabong, Peter Paul (International Journal of Innovative Research in Medical Science, 2020)
Background: Hospital Acquired Infections (HAIs) place a significant economic burden on the healthcare system. Infection control practices are important in minimizing healthcare associated infections. However, low compliance with Universal and Standard Precautions has been reported in a number of studies. The Centre for Disease Control and Prevention (CDC) developed baseline definitions for HAIs that were republished in 2004 and has defined HAIs as those that develop during hospitalization but are neither present nor incubating upon the patient’s admission to the hospital; generally, these infections occur between 48 to 72 hours after admission and within 10 days after hospital discharge. this study aimed at unveiling the level of knowledge, attitude and practices on infection prevention control in the operating theatres by anaesthesia practitioners at TTH. Materials and Methods: A cross-sectional study design was employed. A mixed-method approach was used for data collection which includes a structured questionnaire carried out via face to face interview and observation. Results: The study showed that 100% of the respondents have knowledge on hospital acquired infection control in the theatre in one way or the other whereas attitude and practices toward hospital infection control in the operating theatres are undesirable in some specific areas of infection control such as wearing of sterile gowns and goggle. As high as 80.6% and 69.4% do not wear goggle and gowns respectively whilst performing regional anaesthesia. Conclusions: This study demonstrated that anaesthetists at TTH have reported sub-optimal levels of compliance i.e. attitude and practices with selective infection control. The study further demonstrated that discrepancies exist between anaesthetists’ attitudes towards a guideline as well as their actual practice.